Small RNAs - Big Players in Plant-Microbe Interactions - Huang, Chien-Yu; Wang, Huan; Hu, Po; Hamby, Rachael; Jin, Hailing (Cell host & microbe, 2019)
Eukaryotic small RNAs (sRNAs) are short non-coding regulatory molecules that induce RNA interference (RNAi). During microbial infection, host RNAi machinery is highly regulated and contributes to reprogramming gene expression and balancing plant immunity and growth. While most sRNAs function endogenously, some can travel across organismal boundaries between hosts and microbes and silence genes in trans in interacting organisms, a mechanism called "cross-kingdom RNAi." During the co-evolutionary arms race between fungi and plants, some fungi developed a novel virulence mechanism, sending sRNAs as effector molecules into plant cells to silence plant immunity genes, whereas plants also transport sRNAs, mainly using extracellular vesicles, into the pathogens to suppress virulence-related genes. In this Review, we highlight recent discoveries on these key roles of sRNAs and RNAi machinery. Understanding the molecular mechanisms of sRNA biogenesis, trafficking, and RNAi machinery will help us develop innovative strategies for crop protection.